2000
DOI: 10.1002/1097-4652(200012)185:3<473::aid-jcp19>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the substrate spectrum of the human mismatch‐specific DNA N ‐glycosylase MED1 (MBD4): Fundamental role of the catalytic domain

Abstract: The human DNA repair protein MED1 (also known as MBD4) was isolated as an interactor of the mismatch repair protein MLH1 in a yeast two-hybrid screening. MED1 has a tripartite structure with an N-terminal 5-methylcytosine binding domain (MBD), a central region, and a C-terminal catalytic domain with homology to bacterial DNA damage-specific glycosylases/lyases. Indeed, MED1 acts as a mismatch-specific DNA N-glycosylase active on thymine, uracil, and 5-fluorouracil paired with guanine. The glycosylase activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 33 publications
2
59
0
Order By: Relevance
“…The weak inhibition by ⑀A⅐T and I⅐T might be due to the high K m value of ANPG for these substrates (24 and 69 nM, respectively) (41,42). No significant effect on ⑀A-DNA glycosylase activity of ANPG was detected in the presence of C⅐G, G⅐T, G⅐U, THF⅐G, 8-oxoG⅐C, 8-oxoG⅐A, 5ohU⅐G, DHU⅐G, DHT⅐A, and I⅐T oligonucleotides, even at 8-fold molar excess (lanes 3-8, lanes [13][14][15][16], and data not shown). 2-and 20-fold reductions of the incision were observed in the presence of 1-and 8-fold molar excess of ⑀C⅐G, respectively (lanes [11][12], indicating that ⑀C is a more efficient inhibitor than ⑀A (or Hx) (lanes 10 and 12).…”
Section: Effect Of Duplex Oligonucleotides Containing Single Modifiedmentioning
confidence: 89%
See 2 more Smart Citations
“…The weak inhibition by ⑀A⅐T and I⅐T might be due to the high K m value of ANPG for these substrates (24 and 69 nM, respectively) (41,42). No significant effect on ⑀A-DNA glycosylase activity of ANPG was detected in the presence of C⅐G, G⅐T, G⅐U, THF⅐G, 8-oxoG⅐C, 8-oxoG⅐A, 5ohU⅐G, DHU⅐G, DHT⅐A, and I⅐T oligonucleotides, even at 8-fold molar excess (lanes 3-8, lanes [13][14][15][16], and data not shown). 2-and 20-fold reductions of the incision were observed in the presence of 1-and 8-fold molar excess of ⑀C⅐G, respectively (lanes [11][12], indicating that ⑀C is a more efficient inhibitor than ⑀A (or Hx) (lanes 10 and 12).…”
Section: Effect Of Duplex Oligonucleotides Containing Single Modifiedmentioning
confidence: 89%
“…2 A, schematic representation of the 5Ј-flap structure DNA template containing either a C⅐G or a ⑀C⅐G base pair and possible elongation products: 41-mer, full-sized product; 25-mer, ⑀C termination product; 20-mer, ANPG⅐⑀C termination product; 13-mer, 5Ј-32 P-labeled primer. B, 10 nM 5Ј-32 P-labeled C⅐G (lanes 1-8) and/or ⑀C⅐G (lanes 9 -16) primer/ template were incubated with (lanes 3-8 and lanes [11][12][13][14][15][16] or without (lanes 1-2 and lanes 9 -10) 1 unit of Klenow fragment, and the primer extension reaction was performed for 5 min at 37°C. Lanes 1 and 9, no enzyme; lanes 2 and 10, 500 nM ANPG80; lanes 3 and 11, 10 nM ANPG80; lanes 4 and 12, 20 nM ANPG80; lanes 5 and 13, 50 nM ANPG80; lanes 6 and 14, 100 nM ANPG80; lanes 7 and 15, 200 nM ANPG80; lanes 8 and 16, 500 nM ANPG80.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, in vitro studies have provided contradictory evidence as to whether the presence of a 5-methylcytosine adjacent to a guanine enhances reactivity toward the AFB 1 -epoxide (33,34). It is also possible that an AFB 1 adduct, once formed in a methylated CpG site, is refractory to repair, because methylated sites are often bound by regulatory proteins (e.g., MBD4) (35). Taken together, the hot and cold spots for mutation identified in this work will guide the design of further experiments that will provide mechanistic insights into the pathways by which AFB 1 adducts site-specifically form and are removed in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, analysis of the Mbd4 amino acid sequence revealed that it contained a C-terminal catalytic domain that shares high homology to many known bacterial DNA glycosylases and lyases. Further biochemical analysis using oligonucleotide substrates showed that Mbd4 is a DNA glycosylase that could act in the repair of G-T or G-U mismatches at CpG sites resulting from deamination of 5-methyl cytosine or cytosine, respectively (7,8).…”
mentioning
confidence: 99%